Clear identification of the rare solitary external iliac lymph node metastasis of testicular cancer by using indocyanine green fluorescence guidance. Issue 3 (24th February 2021) - Enei, Yuki; Urabe, Fumihiko; Miki, Jun; Iwatani, Kosuke; Hisakane, Akira; Yasue, Keiji; Yanagisawa, Takafumi; Kimura, Takahiro; Egawa, Shin
Abstract : Introduction: There are few reports on indocyanine green fluorescence‐guided surgery in testis‐related diseases. Case presentation: A 38‐year‐old man underwent orchiectomy for left testicular cancer. Pathological diagnosis was pT1 seminoma. Seven years after the surgery, solitary left external iliac lymph node metastasis was suspected. We decided to perform laparoscopic lymph node dissection combined with indocyanine green fluorescence injection. During the operation, we injected indocyanine green fluorescence into his left inner inguinal ring and found that the lymph node was directly drained from the injection point. The pathological diagnosis of the indocyanine green fluorescence‐positive left external iliac lymph node was testicular cancer metastasis. Conclusion: We experienced a case of solitary left external iliac lymph node recurrence in testicular cancer. Using indocyanine green fluorescence injection, we could visualize the lymphatic drainage route, which helped us identify the lymph node as the primary landing site of metastasis.